Unveiling the Profile of Low-Wage Workers in Indonesia - Lestari Agusalim; Hermanto Siregar; Lukytawati Anggraeni; Sri Mulatsih (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2025)
The low-wage workers play a vital role in supporting in Indonesia's economy but remain highly vulnerable and are often excluded from social protection policies. This study aims to profile low-wage workers and provide insights for policymakers to improve social protection measures. The research utilizes repeated cross-sectional microdata from the National Labor Force Survey (Survei Angkatan Kerja Nasional/Sakernas) between August 2018 and August 2023, a logistic regression model with marginal effects was applied to identify key characteristics of low-wage workers. The findings show that the primary characteristics of low-wage workers are low education levels and working fewer than 20 hours per week. This group is predominantly female, unmarried or divorced, and from younger generations (Gen Z). They are often employed in the informal sector, lacking specific skills, and are mostly working in agriculture. The COVID-19 pandemic worsened their vulnerabilities, amplifying economic risks that persist post-pandemic. The policy implications include expanding educational opportunities to enhance workers' employability, followed by implementing skill training and job placement programs. Additionally, extending minimum wage coverage to both formal and informal sectors, along with offering flexible work arrangements and subsidized childcare, particularly for women, can further support these workers. Furthermore, extending social protection to include social security and healthcare, with incentives for employer contributions, is essential. During crises, policies prioritizing healthcare access, income support, and job protection are crucial for ensuring the economic security of low-wage workers and reducing inequalities.